SUSTAINABILITY STRATEGY FOR DEVELOPMENT OF TILAPIA FISH SEED CULTIVATION BUSINESS WITH BIOFLOC SYSTEM - I Gusti Ngurah Sugiana; I Wayan Arya; Dewa Nyoman Sadguna (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of the study was to determine the sustainability strategy of tilapia seed cultivation with a biofloc system followed by a SWOT matrix so that it was known whether this business could be continued with certain strategies that could be applied. The application of new technology in the form of biofloc technology has been tried in the process of tilapia seed cultivation in Jegu Village, Penebel District, Tabanan Regency, but it is also necessary to study whether the new technology can be implemented sustainably by analyzing it using the SWOT Matrix. This study uses a descriptive method by determining the location by purposive sampling with the consideration that the research site already uses a biofloc system. The results of the SWOT analysis show that the position of cultivators is in quadrant III Turn Around/Stability (Change Strategy) followed by a SWOT matrix based on IFAS (Internal Strategic Factor Analysis Summary) and EFAS (External Strategic Factor Analysis Summary) so that the right strategy is obtained is the WO Strategy namely taking advantage of existing opportunities by improving the internal weaknesses of Mina Ayu group members. So that what needs to be implemented: (1) Cultivators to be able to make maximum use of the capital provided by the capital providing institution, (2) Cultivators to be able to make alternative feeds as a substitute for pellet feed, (3) Cultivators to utilize natural resources that support optimally for increase the number of seeds produced, (4) Cultivators to look for alternative markets other than marketing in Lake Batur to guard against disturbances for cultivators in Lake Batur so as not to interfere with the distribution of the seeds produced, and (5) Cultivators to take advantage of local government policies which supports hatchery activities.